Average Annual Layer Thickness of the WAIS Divide Ice Core from Visual Stratigraphy - Spencer, Matthew (IEDA: US Antarctic Program Data Center, 2015)
Abstract: This data set includes ~50 m averaged annual layer thicknesses down to 3403 m depth at the West Antarctic Ice Sheet (WAIS) Divide ice core as observed visually using diffuse transmitted light opposite a planed surface in a light-shielded booth in the core-processing line at the National Ice Core Lab in Denver, CO.